Connecting Teachers: A Virtual Environment for Networking and Innovation (European Journal of Teaching and Education, 2020)
Educational innovation and collaborative work among teachers are some of the most critical challenges that higher education institutions currently have, especially when the geographical locations of the university’s headquarters are in different places. UNIMINUTO is a university with more than 4700 teachers, present in 64 different locations in Colombia, making the training processes and meetings for teachers a challenging task. The current paper shows the results, and perceived benefits of the Fourth Annual Meeting of Innovative Pedagogical Practices, an online space conceived as an institutional strategy to acknowledge and share innovative experiences inside different learning environments, created by our teachers. The meeting took place through UNIMINUTO YouTube Streaming channel, with the primary goal of increasing access and participation of teachers inside the organization. However, the results showed that even people from other educational organizations and cities interacted in the meeting, increasing the visibility of the teachers and their practices, allowing them to receive feedback from different sources and to create new networks. At the same time, teachers perceived this online strategy as a way to make knowledge available to them, more accessible in terms of times and costs because they could access it without investing in any transportation costs. Those results open the path to transforming those classroom experiences into collaborative educational research, adding value to the institutional strategy towards improving learning outcomes by using didactics that help future professionals develop their skills and competences through didactics and innovation.